2017
DOI: 10.1021/jacs.6b10984
|View full text |Cite
|
Sign up to set email alerts
|

Long-Cycling Aqueous Organic Redox Flow Battery (AORFB) toward Sustainable and Safe Energy Storage

Abstract: Redox flow batteries (RFBs) are a viable technology to store renewable energy in the form of electricity that can be supplied to electricity grids. However, widespread implementation of traditional RFBs, such as vanadium and Zn-Br RFBs, is limited due to a number of challenges related to materials, including low abundance and high costs of redox-active metals, expensive separators, active material crossover, and corrosive and hazardous electrolytes. To address these challenges, we demonstrate a neutral aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
548
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 559 publications
(558 citation statements)
references
References 33 publications
7
548
0
3
Order By: Relevance
“…7,30 Specifically, the R = 1.0 cm 2 and R DC = 1.7 cm 2 ( Figure 10b) are 26-34% lower than suggested targets 7,30 and approach the performance of alkaline or neutral AqRFBs. [79][80][81][82] A recent modeling study of ohmiclimited NAqRFBs, in the limit of fast mass transport at 100% SOC, suggested that the lowest possible ASR would be R DC ≈3.4 cm 2 (≈89 mA cm −2 at 0.3 V overpotential); 38 our experimental work, incorporating realistic mass transfer at 50% SOC, exceeds this predicted performance by >40% for overpotentials <0.3 V.…”
Section: 76mentioning
confidence: 58%
“…7,30 Specifically, the R = 1.0 cm 2 and R DC = 1.7 cm 2 ( Figure 10b) are 26-34% lower than suggested targets 7,30 and approach the performance of alkaline or neutral AqRFBs. [79][80][81][82] A recent modeling study of ohmiclimited NAqRFBs, in the limit of fast mass transport at 100% SOC, suggested that the lowest possible ASR would be R DC ≈3.4 cm 2 (≈89 mA cm −2 at 0.3 V overpotential); 38 our experimental work, incorporating realistic mass transfer at 50% SOC, exceeds this predicted performance by >40% for overpotentials <0.3 V.…”
Section: 76mentioning
confidence: 58%
“…[40][41][42] Considering chemical stability, charged methyl viologen 31,43,44 is known to react with molecular hydrogen, making it unsuitable for use in acidic electrolytes where hydrogen evolution is a likely side reaction. 45 Finally, as for safety, metal polysulfides 27 or ferrocyanide 27,37 can undergo chemical decompositions in acid to produce toxic hydrogen sulfide or cyanide gases, respectively.…”
Section: A3884mentioning
confidence: 99%
“…18 For Na + -and Cl − -IEMs, we estimate membrane conductivity from the high-frequency intercept of full-cell impedance measurements from published flow cells employing these membranes. 27,31 As thick membranes (≥ 120 μm) were employed in the relevant studies, the high-frequency intercept on the experimental Nyquist plot is dominated by the membrane resistance. The conductivity of a NaCl-based RFB electrolyte is taken as an average value from a recent literature study.…”
Section: Estimating Materials Parametersmentioning
confidence: 99%
See 2 more Smart Citations